2023
DOI: 10.1126/sciadv.add7526
|View full text |Cite
|
Sign up to set email alerts
|

Transparent organic upconversion devices displaying high-resolution, single-pixel, low-power infrared images perceived by human vision

Abstract: Crystalline photodiodes remain the most viable infrared sensing technology of choice, yet the opacity and the limitation in pixel size reduction per se restrict their development for supporting high-resolution in situ infrared images. In this work, we propose an all-organic non-fullerene–based upconversion device that brings invisible infrared signal into human vision via exciplex cohost light-emissive system. The device reaches an infrared-to-visible upconversion efficiency of 12.56% by resolving the 940-nm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The efficiency of converting infrared light to visible light is a crucial parameter that characterizes the overall performance of the upconversion device. It is the photon-to-photon conversion efficiency (η con ), also known as the upconversion efficiency of the device. , This parameter calculates the ratio of emitted visible photon number ( N vis ) to the incident infrared photon number ( N IR ) as described in eq . η con = N vis N IR = λ v i s p v i s h c λ I R p I R h c In eq , λ is the wavelength, P is the light power, h is Planck’s constant, and c is the speed of light in vacuum. It is expected that the conversion efficiency relies primarily on the responsivity of the PD and the external quantum efficiency of the LED.…”
Section: Metrics Of Upconversion Imagersmentioning
confidence: 99%
See 3 more Smart Citations
“…The efficiency of converting infrared light to visible light is a crucial parameter that characterizes the overall performance of the upconversion device. It is the photon-to-photon conversion efficiency (η con ), also known as the upconversion efficiency of the device. , This parameter calculates the ratio of emitted visible photon number ( N vis ) to the incident infrared photon number ( N IR ) as described in eq . η con = N vis N IR = λ v i s p v i s h c λ I R p I R h c In eq , λ is the wavelength, P is the light power, h is Planck’s constant, and c is the speed of light in vacuum. It is expected that the conversion efficiency relies primarily on the responsivity of the PD and the external quantum efficiency of the LED.…”
Section: Metrics Of Upconversion Imagersmentioning
confidence: 99%
“…Device designs such as incorporating etalon structures, photonic structures, and so on, are also effective ways to adjust the response spectrum of organic detectors. The light absorption of organic semiconductors can cover a very broad spectrum ranging from ultraviolet to SWIR wavelengths. Benefiting from the photovoltaic field, the organic materials sensitive to visible and near-infrared (NIR) light are very mature. ,,, Organic materials with sensitivity to SWIR wavelengths are still under development. ,, It is reported that organic semiconductors with abundant midgap states tend to respond to thermal signals with wavelengths located in the midwave and long-wave infrared . These results are encouraging for the design of organic upconversion imagers for different wavebands.…”
Section: Metrics Of Upconversion Imagersmentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc oxide treated with perylene diimides functionalized with amino oxide (PDINO) was introduced to suppress the leakage current by barrier lowering from the external bias regardless of the infrared illumination. A non-fullerene acceptor, with an energy bandgap of 1.10 eV (cutoff wavelength around 1150 nm), was incorporated into the CGL to form a donor: acceptor bulk heterojunction blend (D: A BHJ) [33]. We chose TAPC as the interfacial contact layer between CGL and a typical phosphorescent light-emitting layer to enforce the charge selectivity.…”
Section: Introductionmentioning
confidence: 99%